(adsbygoogle = window.adsbygoogle || []).push({}); 1. The problem statement, all variables and given/known data

y = 3*cube root 3√(x^{2}-1)

2. Relevant equations

Udu/dx + Vdv/dx (wrong as per below)

Chain Rule now used

3. The attempt at a solution

I have:

Now y = 3*(x^{2}-1)^1/3

let z=x^{2}-1 y= 3(z)^1/3

dz/dx = 2x dy/dz = z^-2/3 = (x^{2}-1)^-2/3

all = dy/dx = dz/dx * dy/dz = 2x*(x^{2}-1)^-2/3 = 2x/(x^{2}-1)^2/3

Instead I have an answer in my book:

dy/dx = 3*1/3(x^{2}-1)^-2/3

which in the end = (x^{2}-1)^-2/3

I believe my answer is correct and it is a typing mistake, but I am not 100% sure.

Thank you for any help in advance.

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Differentiate with respect to x

**Physics Forums | Science Articles, Homework Help, Discussion**